2017
DOI: 10.1007/s10862-017-9624-8
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, Repetitive Negative Thinking, and Depressive Symptoms in Early Adolescence: a Prospective Study

Abstract: Repetitive negative thinking (RNT) is a transdiagnostic vulnerability factor, involved in the maintenance of a variety of emotional problems. Recently, the Perseverative Thinking Questionnaire -Child version (PTQ-C) was developed as a content-independent measure of RNT in children and adolescents. The current study investigated the reliability and predictive validity of the PTQ-C and examined temperament as a developmental predictor of RNT. For this end, 701 early adolescents completed measures of RNT, depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…However, the dimensions of the latter model were very strongly correlated (between .86 and .94), so the one-factor model was finally selected because of its parsimony. This factor solution has been replicated in the study by Bijttebier et al (2018), which also showed that the PTQ-C scores longitudinally predicted depressive symptoms even when controlling baseline symptomatology.…”
mentioning
confidence: 68%
“…However, the dimensions of the latter model were very strongly correlated (between .86 and .94), so the one-factor model was finally selected because of its parsimony. This factor solution has been replicated in the study by Bijttebier et al (2018), which also showed that the PTQ-C scores longitudinally predicted depressive symptoms even when controlling baseline symptomatology.…”
mentioning
confidence: 68%
“…For example, in a longitudinal cohort study in 658 at-risk adolescents Wilkinson et al (9) found that RNT predicted both the onset of a depressive episode and levels of depressive symptoms over a 12month interval, when controlled for baseline symptomatology. Likewise, Bijttebier and colleagues (10) showed that, again when controlled for baseline symptom levels, RNT predicted prospective levels of depressive symptoms at 3-month follow-up in 701 adolescents.…”
Section: Introductionmentioning
confidence: 93%
“…For the one-factor model, all 15 PTQ-C items were loaded onto the one latent variable, as in Bijttebier et al (2018), v 2 (90) = 206.27, p < .001, CFI = 0.88, RMSEA = 0.11, 90% CI [0.09, 0.12], RMSEA test of close fit p < .001. Results suggested that for the one-factor model, the hypothesis of both perfect fit and close fit were rejected.…”
Section: Confirmatory Factor Analysismentioning
confidence: 99%